Business sustainability performance and cost of equity capital - Ng, Anthony C.; Rezaee, Zabihollah (Journal of Corporate Finance, 2015)
Business sustainability has emerged as the theme of the 21st century. We examine whether and how different components of economic sustainability disclosure (ECON), as well as environmental, social, and governance (ESG) dimensions of sustainability performance affect cost of equity, individually and in aggregate. In addition, we investigate whether and how ECON and ESG sustainability interactively affect cost of equity capital. Costs of equity are calculated using industry adjusted earnings–price ratios and finite horizon expected return model. Using a sample of more than 3000 firms during 1990–2013, we find that ECON (ESG) is negatively associated with cost of equity, but only growth and research (environmental and governance) sustainability performance dimensions contribute to this relationship. Operation efficiency is positively, while social sustainability performance is only marginally, related to cost of equity. We also find that ECON and ESG sustainability performance interactively affect cost of equity. In general, the relationship between ECON (ESG) and cost of capital is strengthened when ESG (ECON) performance is strong.